2019
DOI: 10.3390/cancers11040550
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Adjuvant Chemotherapy and Survival in Colorectal, Gastric, and Pancreatic Cancer. A Systematic Review and Meta-Analysis

Abstract: (1) Background: The optimal timing of adjuvant chemotherapy (CT) in gastrointestinal malignancies is still a matter of debate. For colorectal cancer, it is recommended to start post-operative treatment within eight weeks. The objective of this study was to assess the clinical effects of starting adjuvant CT within or after 6–8 weeks post-surgery in colorectal, gastric, and pancreatic cancer. (2) Methods: MEDLINE, EMBASE, and the Cochrane Library were searched in December 2018. Publications comparing the outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 47 publications
1
49
1
1
Order By: Relevance
“…Despite major progress in the diagnosis and treatment of early gastric cancer (EGC), gastric cancer remains the second most frequent cause of cancer death globally [1,2]. To date, endoscopic mucosal resection and endoscopic submucosal dissection are the 2 ideal curative treatments for EGC, and no significant difference in mortality and survival rate between endoscopic surgery and open surgery was observed [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Despite major progress in the diagnosis and treatment of early gastric cancer (EGC), gastric cancer remains the second most frequent cause of cancer death globally [1,2]. To date, endoscopic mucosal resection and endoscopic submucosal dissection are the 2 ideal curative treatments for EGC, and no significant difference in mortality and survival rate between endoscopic surgery and open surgery was observed [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis showed a survival benefit when AC was started within 6 to 8 weeks of surgery. However, when AC was started after 8 weeks, a 20% increased risk of death was observed (27). Notwithstanding, this meta-analysis did not evaluate solely gastric cancer, but also included other types of cancer such as colorectal or pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant therapy should be initiated as soon as patient has recovered from surgery with complete healing of surgical wounds which usually takes about 2-4 weeks. A meta-analysis in 2019 which included 34 comparative studies of resected colon cancer reported that delay in treatment beyond 6-8 weeks was associated with inferior survival (HR 1.27,95% CI 1.21-1.33; p < 0.001) [50]. Another review which included more than 15,000 patients concluded that a 4-week increase in time to initiate adjuvant chemotherapy was associated with a 14% relative decrease in disease free survival and overall survival [51].…”
Section: Timing Of Chemotherapymentioning
confidence: 99%